Distribution of Camphor Monooxygenase Genes in Soil Bacteria - N, Ngadiman; Suenaga, Hikaru; Goto, Masatoshi; Furukawa, Kensuke (Universitas Gadjah Mada, 2005)
In microbial degradation of camphor, the first step is oxidation by multiunit enzyme, camphormonooxygenase, encoded by cam genes (camA,B,C). Seven camphor-utilizing bacterial strains have been isolatedfrom soil at various locations. CamA,B,C genes of Pseudomonas putida strain PpG1 and strain GF2001 were used asprobes to explore their abundance in the camphor-utilizing bacteria. Southern analysis revealed that all of thecam genes of GF2001 could hybridize well to the SpeI-digested genomic DNA of strains tested, whereas PpG1 camgenes were not. This result suggested that the GF2001 type cam genes are widely distributed among the camphorutilizingstrains in the environment. Thus strain GF2001 and seven newly isolated strains share a commonevolutionary origin.Key words: Camphor monooxygenase genes, gene distribution, sail bacteria.